Distinct processing of ambiguous speech in people with non-clinical auditory verbal hallucinations - Alderson-Day, B; Lima, C; Evans, S; Krishnan, S; Shanmugalingam, P; Fernyhough, C; Scott, S (Oxford University Press, 2017)
Auditory verbal hallucinations (hearing voices) are typically associated with psychosis, but a minority of the general population also experience them frequently and without distress. Such ‘non-clinical’ experiences offer a rare and unique opportunity to study hallucinations apart from confounding clinical factors, thus allowing for the identification of symptom-specific mechanisms. Recent theories propose that hallucinations result from an imbalance of prior expectation and sensory information, but whether such an imbalance also influences auditory-perceptual processes remains unknown. We examine for the first time the cortical processing of ambiguous speech in people without psychosis who regularly hear voices. Twelve non-clinical voice-hearers and 17 matched controls completed a functional magnetic resonance imaging scan while passively listening to degraded speech (‘sine-wave’ speech), that was either potentially intelligible or unintelligible. Voice-hearers reported recognizing the presence of speech in the stimuli before controls, and before being explicitly informed of its intelligibility. Across both groups, intelligible sine-wave speech engaged a typical left-lateralized speech processing network. Notably, however, voice-hearers showed stronger intelligibility responses than controls in the dorsal anterior cingulate cortex and in the superior frontal gyrus. This suggests an enhanced involvement of attention and sensorimotor processes, selectively when speech was potentially intelligible. Altogether, these behavioural and neural findings indicate that people with hallucinatory experiences show distinct responses to meaningful auditory stimuli. A greater weighting towards prior knowledge and expectation might cause non-veridical auditory sensations in these individuals, but it might also spontaneously facilitate perceptual processing where such knowledge is required. This has implications for the understanding of hallucinations in clinical and non-clinical populations, and is consistent with current ‘predictive processing’ theories of psychosis.